Effective biodegradation of chlorophenols, sulfonamides, and their mixtures by bacterial laccase immobilized on chitin - Jianhui Chen; Jiashu Liu; Bixin Chen; Fan Yang; Bianxia Li; Huanan Li; Zhengbing Jiang; Huiting Song (Ecotoxicology and Environmental Safety, 2023)
Coexisting multi-pollutants like sulfonamides (SAs) and chlorophenols (CPs) in the ecological environment pose a potential risk to living organisms. The development of a strategy for the effective removal of multiple pollutants has become an urgent need. Herein, we systematically investigated the potential of immobilized bacterial laccase to remove chlorophenols (CPs), sulfonamides (SAs), and their mixtures. Laccase from Bacillus pumilus ZB1 was efficiently immobilized on chitin and its thermal stability, pH stability, and affinity to substrates were improved. Reusability assessment showed the immobilized laccase retained 75.5% of its initial activity after five cycles. The removal efficiency of CPs and SAs by immobilized laccase was significantly improved compared with that of free laccase. In particular, the removal of 2,4-dichlorophenol and 2,4,6-trichlorophenol reached 96.9% and 89.3% respectively within 8 h. The immobilized laccase could remove 63.70% of 2,4-dichlorophenol after four cycles. The degradation pathways of 2,4-dichlorophenol and sulfamethazine were proposed via LC/MS analysis. When the co-pollutants containing 2,4,6-trichlorophenol and sulfamethoxazole, immobilized laccase showed 100% removal of 2,4,6-trichlorophenol and 38.71% removal of sulfamethoxazole simultaneously. Cytotoxicity and phytotoxicity tests indicated that immobilized laccase can alleviate the toxicity of co-pollutants. The results demonstrate that chitin-based laccase immobilization can be an effective strategy for the removal of SAs, CPs, and their co-pollutants.